ZnSe-coated ZnO nano semiconductor composite heterojunction and preparation method thereof

The preparation of ZnSe@ZnO nanosemiconductor composite heterojunction through alcoholylation reaction and chemical vapor deposition technology solves the cost and pollution problems of equipment, improves the photoelectric performance and production efficiency of nanosemiconductor materials, and promotes the development of new electronic devices.

CN119118529AInactive Publication Date: 2024-12-13XIAN UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411201101.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as expensive and easy contamination in the preparation of ZnSe@ZnO nano-semiconductor composites, which affects the performance and production efficiency of materials.

Method used

ZnO sol was prepared by alcoholylation reaction of zinc acetate dihydrate and ethylene glycol methyl ether. After coating on the FTO substrate, annealing was performed to form a ZnO seed layer. Then, zinc nitrate hexahydrate and hexamethyltetramine were mixed. The precursor solution was reacted and combined with the chemical reaction of selenium powder and sodium borohydride to prepare ZnSe@ZnO nanosemiconductor composite heterojunction.

Benefits of technology

The preparation of nano-semiconductor composite materials without using expensive equipment and avoiding contamination has been achieved, which significantly improves the photoelectric sensitivity and photoelectric performance, and promotes the development of new electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118529A_ABST
    Figure CN119118529A_ABST
Patent Text Reader

Abstract

The invention relates to the field of nanometer optoelectronic materials, in particular to a ZnSe-ZnO nanometer semiconductor composite heterojunction and a preparation method thereof.The preparation method comprises the following steps that zinc acetate dihydrate and ethylene glycol monomethyl ether are mixed to prepare ZnO sol; coating the ZnO sol on an FTO substrate, and carrying out annealing treatment to obtain the FTO substrate on which a ZnO seed layer grows; mixing zinc nitrate hexahydrate and hexamethylenetetramine to obtain a precursor solution, adding the precursor solution into the FTO substrate on which the ZnO seed layer grows, and reacting to obtain the FTO substrate on which the ZnO nanorod array grows; the preparation method comprises the following steps: mixing selenium powder, water and sodium borohydride to obtain a transparent solution, immersing an FTO substrate on which a ZnO nanorod array grows into the transparent solution, and reacting at 45-55 DEG C to obtain the ZnSe-ZnO nano semiconductor composite heterojunction. The nano semiconductor composite heterojunction disclosed by the invention can greatly improve the optical performance of a nano semiconductor device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano-photoelectronic materials, and in particular to a ZnSe@ZnO nano-semiconductor composite heterojunction and a preparation method thereof. Background Art

[0002] Nowadays, nanotechnology has penetrated into every aspect of our lives, and further exploration of nanomaterials has become the focus of current research. Among them, nano-semiconductor heterojunctions, as an important nanostructure, have become a hot topic due to their excellent physical properties and wide application fields. Among the many semiconductor materials, II-VI semiconductors and their alloys have the advantages of large bandwidth, direct band transition, large exciton binding energy, and alloys in any proportion, which makes them have a wide range of application potentials in the optoelectronic field.

[0003] Among the II-VI semiconductor materials, ZnO nanomaterials are the most representative wide bandgap semiconductor materials. Due to their high carrier migration speed, good physical and chemical stability, high thermal conductivity and low thermal expansion coefficient, especially high exciton binding energy, one-dimensional ZnO nanosemiconductor materials have been widely used in optoelectronic devices such as gas sensors, photodiodes, solar cells, and photodetectors. ZnSe is also an important member of the II-VI wide bandgap semiconductors. Its valence band and conduction band are intertwined with those of ZnO, so it can be well combined with ZnO to form a ZnSe@ZnO nanosemiconductor composite heterojunction structure.

[0004] The existing technology generally adopts chemical vapor deposition technology to prepare ZnSe@ZnO nano-semiconductor composite materials, which has problems such as expensive equipment and easy pollution during the preparation process. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a ZnSe@ZnO nano-semiconductor composite heterojunction and a preparation method thereof. The present invention can improve the performance of nano-semiconductor materials, promote the production of new electronic devices, and expand research in the field of materials science, promote the further development of the semiconductor industry and technological progress, and also contribute to social and economic development.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for preparing a ZnSe@ZnO nano-semiconductor composite heterojunction comprises the following steps:

[0008] Zinc acetate dihydrate and ethylene glycol methyl ether are mixed, and a stabilizer, ethanolamine, is added thereto to cause an alcoholysis reaction to obtain a ZnO sol. The specific reaction equation is as follows:

[0009]

[0010]

[0011] Zn(OH)2→ZnO+H2O (3)

[0012] The ZnO sol is coated on the FTO substrate, and then annealed to obtain a crystalline ZnO seed layer, which is beneficial to the subsequent growth of the ZnO nanorod array, thereby obtaining an FTO substrate with a ZnO seed layer grown thereon;

[0013] Zinc nitrate hexahydrate and hexamethylenetetramine are mixed to obtain a precursor solution, and the precursor solution is added to a FTO substrate having a ZnO seed layer grown thereon, and then reacted to grow a ZnO nanorod array on the surface of the ZnO seed layer, thereby obtaining a FTO substrate having a ZnO nanorod array grown thereon. The specific reaction equation is as follows:

[0014]

[0015]

[0016]

[0017]

[0018]

[0019] Mix selenium powder, water and sodium borohydride. Sodium borohydride is a strong reducing agent, which reduces selenium to Se 2- , obtaining a transparent solution, immersing the FTO substrate grown with the ZnO nanorod array in the transparent solution, and finally subjecting the aqueous solution to a chemical reaction at 45 to 55° C. for 30 to 60 minutes to obtain a ZnSe@ZnO nano-semiconductor composite heterojunction.

[0020] In a preferred embodiment of the present invention, during the preparation of ZnO sol, the usage ratio of zinc acetate dihydrate and ethylene glycol methyl ether is 0.26 g:25 mL.

[0021] In a preferred embodiment of the present invention, in the precursor solution, the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 1:3.

[0022] In a preferred embodiment of the present invention, the usage ratio of selenium powder, water and sodium borohydride is 6-18 mg:20 mL:23-55.2 mg.

[0023] In a preferred embodiment of the present invention, the annealing temperature of the seed layer is 400-450° C., the annealing time is 70 minutes, and the heating rate is 6° C. / min.

[0024] In a preferred embodiment of the present invention, the reaction temperature of the precursor solution and the FTO substrate on which the ZnO seed layer is grown is 90°C to 110°C.

[0025] In a preferred embodiment of the present invention, the reaction time between the precursor solution and the FTO substrate on which the ZnO seed layer is grown is 4 to 6 hours.

[0026] In a preferred embodiment of the present invention, the ZnO sol is coated by spin coating at 700 rpm, 1500 rpm and 3500 rpm, respectively, and each spin coating time is 10 s.

[0027] Another object of the present invention is to provide a ZnSe@ZnO nano-semiconductor composite heterojunction prepared by any of the preparation methods described above.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention provides a ZnSe@ZnO nano-semiconductor composite heterojunction and a preparation method thereof. Zinc acetate dihydrate and ethylene glycol methyl ether are used as raw materials to undergo alcoholysis reaction to prepare ZnO sol, and the ZnO sol is coated on an FTO substrate, and then annealing treatment is performed to obtain an FTO substrate with a ZnO seed layer grown thereon; then zinc nitrate hexahydrate and hexamethylenetetramine are mixed to obtain a precursor solution, and the precursor solution is added to the FTO substrate with the ZnO seed layer grown thereon to react, so that the ZnO nanorod array is formed on the ZnO seed layer. The method comprises the following steps: growing ZnO nanorods on the surface to obtain an FTO substrate with a ZnO nanorod array; mixing selenium powder, water and a reducing agent, sodium borohydride, to obtain a transparent solution, immersing the FTO substrate with the ZnO nanorod array in the transparent solution, and finally reacting at 45 to 55° C. for 30 to 60 minutes to obtain a ZnSe@ZnO nano-semiconductor composite heterojunction. The preparation method of the invention does not use expensive equipment and does not have pollution problems. The obtained ZnSe@ZnO nano-semiconductor composite heterojunction optoelectronic device has excellent photoelectric sensitivity.

[0030] 2. The heterojunction structure composed of ZnSe and ZnO nano-semiconductors of the present invention can significantly increase the separation speed of photogenerated carriers and reduce the recombination efficiency of carriers, thereby greatly improving the photoelectric performance of nano-semiconductor devices. When the temperature is 45°C and 55°C, the peak of Se single substance marked in red does not appear in the XRD diagram of the sample, indicating that there is a heterostructure in the material. When the temperature is 55°C, the dark current of the ZnO / ZnSe composite nanorod array photoelectric device is 2.9×10 - 5 A, the photocurrent is 8.31×10 -3 A, the photoelectric response sensitivity is 2868.3.

[0031] 3. The research significance of this invention lies not only in improving the performance of nano-semiconductor materials and promoting the production of new electronic devices, but also in expanding the research in the field of materials science, promoting the further development of the semiconductor industry and technological progress, and at the same time contributing to social and economic development. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 XRD patterns of ZnO / ZnSe composite nanorod arrays at different solution temperatures of the present invention, (a) 45°C, (b) 55°C, (c) 65°C, and (d) 75°C.

[0033] Figure 2 These are SEM images of the ZnO / ZnSe nanoarray composite material of the present invention at different temperatures, (a1) to (a2) 45°C, (b1) to (b2) 55°C, (c1) to (c2) 65°C, and (d1) to (d2) 75°C.

[0034] Figure 3 XPS results of the ZnO / ZnSe composite nanorod array prepared at 55°C in the present invention, (a) Suvery, (b) Zn2p, (c) Se3d spectrum, (d) O1s spectrum.

[0035] Figure 4 XPS results of the ZnO / ZnSe nanoarray composite material prepared at 75°C of the present invention, (a) Suvery, (b) Zn2p, (c) Se3d spectrum, (d) O1s spectrum.

[0036] Figure 5 The graph is a test curve of the photoelectric performance of the ZnO / ZnSe composite nanorod array photoelectric device at different temperatures of the present invention, and a current-time curve diagram with or without ultraviolet light at a bias voltage of -1V. DETAILED DESCRIPTION

[0037] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0039] Example 1

[0040] A method for preparing a ZnSe@ZnO nano-semiconductor composite heterojunction comprises the following steps:

[0041] (1) Preparation of ZnO sol: First, 25 mL of ethylene glycol methyl ether was measured and placed in a clean beaker. Then, 0.26 g of zinc acetate dihydrate was placed in the beaker. The prepared solution was transferred to a magnetic stirrer and stirred thoroughly and evenly for 30 minutes. The solution then became white and turbid. At this time, ethanolamine was slowly added as a stabilizer to make the solution transparent. Finally, the transparent solution was transferred to a 70°C oven and concentrated to 15 mL to form a yellow transparent ZnO sol with a certain viscosity.

[0042] (2) Preparation of ZnO seed layer: FTO was cleaned in an ultrasonic cleaner with acetone, anhydrous ethanol and deionized water for 20 minutes respectively. The cleaned FTO was then placed on a coater and coated with ZnO sol. The coating was performed at low speed (700 rpm), medium speed (1500 rpm) and high speed (3500 rpm). Each spin coating took 10 seconds. The spin-coated sample was placed in an oven at 80°C for 10 minutes. The spin coating and drying process was repeated four times. Subsequently, the sample was placed in a muffle furnace for annealing. The temperature was raised to 400°C at a rate of 6°C / min, maintained for 70 minutes, and finally naturally cooled to room temperature.

[0043] (3) Preparation of ZnO nanorod arrays: First, pour 0.04 mol of zinc nitrate hexahydrate and 0.12 mol of hexamethylenetetramine solution into a beaker at a molar ratio of 1:3. Place them on a magnetic stirrer and stir for 30 minutes. Then, use a rubber-tipped dropper to drop the zinc nitrate hexahydrate solution into the hexamethylenetetramine solution. Continue stirring for 30 minutes to promote the reaction and finally obtain a precursor solution. Next, add 35 mL (70% by volume) of the precursor solution to a reactor containing an FTO substrate on which a ZnO seed layer is grown. Then, seal the reactor and react at 90°C for 4 hours to allow the ZnO nanorod array to grow on the surface of the ZnO seed layer. After the reaction is completed, wash the sample with deionized water to remove residual drugs and impurities. Finally, place the sample in an oven at 80°C to dry for use.

[0044] (4) Preparation of ZnSe@ZnO nano-semiconductor composite heterojunction: Add 12 mg of selenium powder, 20 mL of deionized water and 46 mg of sodium borohydride to a small beaker, then place the small beaker into a large beaker filled with deionized water. The liquid level of the large beaker should be higher than that of the small beaker. After the temperature of the magnetic stirrer stabilizes at 55°C, stir for 30 minutes. A transparent solution will be obtained. Then, immerse the reverse side of the ZnO nanorod array grown on the FTO substrate in the above transparent solution and store it in an environment at a temperature of 55°C for 1 hour. After the reaction is completed, wash it with deionized water and finally dry it in air. Thus, a ZnSe@ZnO nano-semiconductor composite heterojunction is successfully obtained, which is recorded as ZS-2.

[0045] Example 2

[0046] A method for preparing a ZnSe@ZnO nano-semiconductor composite heterojunction comprises the following steps:

[0047] (1) Preparation of ZnO sol: First, 25 mL of ethylene glycol methyl ether was measured and placed in a clean beaker. Then, 0.26 g of zinc acetate dihydrate was placed in the beaker. The prepared solution was transferred to a magnetic stirrer and stirred thoroughly and evenly for 30 minutes. The solution then became white and turbid. At this time, ethanolamine was slowly added as a stabilizer to make the solution transparent. Finally, the transparent solution was transferred to a 70°C oven and concentrated to 15 mL to form a yellow transparent ZnO sol with a certain viscosity.

[0048] (2) Preparation of ZnO seed layer: FTO was cleaned in an ultrasonic cleaner with acetone, anhydrous ethanol and deionized water for 20 minutes respectively. The cleaned FTO was then placed on a coater and coated with ZnO sol. The coating was performed at low speed (700 rpm), medium speed (1500 rpm) and high speed (3500 rpm). Each spin coating took 10 seconds. The spin-coated sample was placed in an oven at 80°C for 10 minutes. The spin coating and drying process was repeated four times. Subsequently, the sample was placed in a muffle furnace for annealing. The temperature was raised to 400°C at a rate of 6°C / min, maintained for 70 minutes, and finally naturally cooled to room temperature.

[0049] (3) Preparation of ZnO nanorod arrays: First, pour 0.04 mol of zinc nitrate hexahydrate and 0.12 mol of hexamethylenetetramine solution into a beaker, respectively, with a molar ratio of 1:3. Place them on a magnetic stirrer and stir for 30 minutes. Then, use a rubber-tipped dropper to drop the zinc nitrate hexahydrate solution into the hexamethylenetetramine solution. Continue stirring for 30 minutes to promote the reaction and finally obtain a precursor solution. Next, add 35 mL (70% by volume) of the precursor solution to a reactor containing an FTO substrate on which a ZnO seed layer is grown. Then, place the reactor in a sealed state and react at 90°C for 4 hours to allow the ZnO nanorod array to grow on the surface of the ZnO seed layer. After the reaction is completed, wash the sample with deionized water to remove residual drugs and impurities. Finally, place the sample in an oven at 80°C to dry for use.

[0050] (4) Preparation of ZnSe@ZnO nano-semiconductor composite heterojunction: Add 12 mg of selenium powder, 20 mL of deionized water and 46 mg of sodium borohydride to a small beaker, then place the small beaker into a large beaker filled with deionized water. The liquid level of the large beaker should be higher than that of the small beaker. After the temperature of the magnetic stirrer stabilizes at 55°C, stir for 30 minutes. A transparent solution will be obtained. Then, immerse the reverse side of the ZnO nanorod array grown on the FTO substrate in the above transparent solution and store it in an environment at a temperature of 45°C for 1 hour. After the reaction is completed, wash it with deionized water and finally dry it in air. Thus, a ZnSe@ZnO nano-semiconductor composite heterojunction is successfully obtained, which is recorded as ZS-1.

[0051] Example 3

[0052] A method for preparing a ZnSe@ZnO nano-semiconductor composite heterojunction comprises the following steps:

[0053] (1) Preparation of ZnO sol: First, 25 mL of ethylene glycol methyl ether was measured and placed in a clean beaker. Then, 0.26 g of zinc acetate dihydrate was placed in the beaker. The prepared solution was transferred to a magnetic stirrer and stirred thoroughly and evenly for 30 minutes. The solution then became white and turbid. At this time, ethanolamine was slowly added as a stabilizer to make the solution transparent. Finally, the transparent solution was transferred to a 70°C oven and concentrated to 15 mL to form a yellow transparent ZnO sol with a certain viscosity.

[0054] (2) Preparation of ZnO seed layer: FTO was cleaned in an ultrasonic cleaner with acetone, anhydrous ethanol and deionized water for 20 minutes respectively. The cleaned FTO was then placed on a coater and coated with ZnO sol. The coating was performed at low speed (700 rpm), medium speed (1500 rpm) and high speed (3500 rpm). Each spin coating took 10 seconds. The spin-coated sample was placed in an oven at 80°C for 10 minutes. The spin coating and drying process was repeated four times. Subsequently, the sample was placed in a muffle furnace for annealing. The temperature was raised to 420°C at a rate of 6°C / min, maintained for 70 minutes, and finally naturally cooled to room temperature.

[0055] (3) Preparation of ZnO nanorod arrays: First, pour 0.04 mol of zinc nitrate hexahydrate and 0.12 mol of hexamethylenetetramine solution into a beaker at a molar ratio of 1:3. Place them on a magnetic stirrer and stir for 30 minutes. Then, use a rubber-tipped dropper to drop the zinc nitrate hexahydrate solution into the hexamethylenetetramine solution. Continue stirring for 30 minutes to promote the reaction and finally obtain a precursor solution. Next, add 35 mL (70% by volume) of the precursor solution to a reactor containing an FTO substrate on which a ZnO seed layer is grown. Then, seal the reactor and react at 100°C for 6 hours to allow the ZnO nanorod array to grow on the surface of the ZnO seed layer. After the reaction is completed, wash the sample with deionized water to remove residual drugs and impurities. Finally, place the sample in an oven at 80°C to dry for later use.

[0056] (4) Preparation of ZnSe@ZnO nano-semiconductor composite heterojunction: Add 6 mg of selenium powder, 20 mL of deionized water and 23 mg of sodium borohydride to a small beaker, then place the small beaker into a large beaker filled with deionized water. The liquid level of the large beaker should be higher than that of the small beaker. After the temperature of the magnetic stirrer stabilizes at 55°C, stir for 30 minutes. A transparent solution will be obtained. Then, immerse the reverse side of the ZnO nanorod array grown on the FTO substrate in the above transparent solution and store it in an environment at a temperature of 55°C for 30 minutes. After the reaction is completed, wash it with deionized water and finally dry it in air. Thus, a ZnSe@ZnO nano-semiconductor composite heterojunction is successfully obtained.

[0057] Example 4

[0058] A method for preparing a ZnSe@ZnO nano-semiconductor composite heterojunction comprises the following steps:

[0059] (1) Preparation of ZnO sol: First, 25 mL of ethylene glycol methyl ether was measured and placed in a clean beaker. Then, 0.26 g of zinc acetate dihydrate was placed in the beaker. The prepared solution was transferred to a magnetic stirrer and stirred thoroughly and evenly for 30 minutes. The solution then became white and turbid. At this time, ethanolamine was slowly added as a stabilizer to make the solution transparent. Finally, the transparent solution was transferred to a 70°C oven and concentrated to 15 mL to form a yellow transparent ZnO sol with a certain viscosity.

[0060] (2) Preparation of ZnO seed layer: FTO was cleaned in an ultrasonic cleaner with acetone, anhydrous ethanol and deionized water for 20 minutes respectively. The cleaned FTO was then placed on a coater and coated with ZnO sol. The coating was performed at low speed (700 rpm), medium speed (1500 rpm) and high speed (3500 rpm). Each spin coating took 10 seconds. The spin-coated sample was placed in an oven at 80°C for 10 minutes. The spin coating and drying process was repeated four times. Subsequently, the sample was placed in a muffle furnace for annealing. The temperature was raised to 450°C at a rate of 6°C / min, maintained for 70 minutes, and finally naturally cooled to room temperature.

[0061] (3) Preparation of ZnO nanorod arrays: First, pour 0.04 mol of zinc nitrate hexahydrate and 0.12 mol of hexamethylenetetramine solution into a beaker at a molar ratio of 1:3. Place them on a magnetic stirrer and stir for 30 minutes. Then, use a rubber-tipped dropper to drop the zinc nitrate hexahydrate solution into the hexamethylenetetramine solution. Continue stirring for 30 minutes to promote the reaction and finally obtain a precursor solution. Next, add 35 mL (70% by volume) of the precursor solution to a reactor containing an FTO substrate on which a ZnO seed layer is grown. Then, seal the reactor and react at 110°C for 5 hours to allow the ZnO nanorod array to grow on the surface of the ZnO seed layer. After the reaction is completed, wash the sample with deionized water to remove residual drugs and impurities. Finally, place the sample in an oven at 80°C to dry for later use.

[0062] (4) Preparation of ZnSe@ZnO nano-semiconductor composite heterojunction: Add 18 mg of selenium powder, 20 mL of deionized water and 55.2 mg of sodium borohydride to a small beaker, then place the small beaker into a large beaker filled with deionized water. The liquid level of the large beaker should be higher than that of the small beaker. After the temperature of the magnetic stirrer stabilizes at 55°C, stir for 30 minutes. A transparent solution will be obtained. Then, immerse the reverse side of the ZnO nanorod array grown on the FTO substrate in the above transparent solution and store it in an environment at a temperature of 55°C for 45 minutes. After the reaction is completed, wash it with deionized water and finally dry it in air. Thus, a ZnSe@ZnO nano-semiconductor composite heterojunction is successfully obtained.

[0063] Comparative Example 1

[0064] A method for preparing a ZnSe@ZnO nano-semiconductor composite material comprises the following steps:

[0065] (1) Preparation of ZnO sol: First, 25 mL of ethylene glycol methyl ether was measured and placed in a clean beaker. Then, 0.26 g of zinc acetate dihydrate was placed in the beaker. The prepared solution was transferred to a magnetic stirrer and stirred thoroughly and evenly for 30 minutes. The solution then became white and turbid. At this time, ethanolamine was slowly added as a stabilizer to make the solution transparent. Finally, the transparent solution was transferred to a 70°C oven and concentrated to 15 mL to form a yellow transparent ZnO sol with a certain viscosity.

[0066] (2) Preparation of ZnO seed layer: FTO was cleaned in an ultrasonic cleaner with acetone, anhydrous ethanol and deionized water for 20 minutes respectively. The cleaned FTO was then placed on a coater and coated with ZnO sol. The coating was performed at low speed (700 rpm), medium speed (1500 rpm) and high speed (3500 rpm). Each spin coating took 10 seconds. The spin-coated sample was placed in an oven at 80°C for 10 minutes. The spin coating and drying process was repeated four times. Subsequently, the sample was placed in a muffle furnace for annealing. The temperature was raised to 400°C at a rate of 6°C / min, maintained for 70 minutes, and finally naturally cooled to room temperature.

[0067] (3) Preparation of ZnO nanorod arrays: First, pour 0.04 mol of zinc nitrate hexahydrate and 0.12 mol of hexamethylenetetramine solution into a beaker at a molar ratio of 1:3. Place them on a magnetic stirrer and stir for 30 minutes. Then, use a rubber-tipped dropper to drop the zinc nitrate hexahydrate solution into the hexamethylenetetramine solution. Continue stirring for 30 minutes to promote the reaction and finally obtain a precursor solution. Next, add 35 mL (70% by volume) of the precursor solution to a reactor containing an FTO substrate on which a ZnO seed layer is grown. Then, place the reactor in a sealed state and react at 90°C for 4 hours to allow the ZnO nanorod array to grow on the surface of the ZnO seed layer. After the reaction is completed, wash the sample with deionized water to remove residual drugs and impurities. Finally, place the sample in an oven at 80°C to dry for use.

[0068] (4) Preparation of ZnSe@ZnO nano-semiconductor composite heterojunction: Add 12 mg of selenium powder, 20 mL of deionized water and 46 mg of sodium borohydride to a small beaker, then place the small beaker into a large beaker filled with deionized water. The liquid level of the large beaker should be higher than that of the small beaker. After the temperature of the magnetic stirrer stabilizes at 55°C, stir for 30 minutes. A transparent solution will be obtained. Then, immerse the reverse side of the ZnO nanorod array grown on the FTO substrate in the above transparent solution and store it in an environment at 65°C for 1 hour. After the reaction is completed, wash it with deionized water and finally dry it in air. Thus, a ZnSe@ZnO nano-semiconductor composite heterojunction is successfully obtained, which is recorded as ZS-3.

[0069] Comparative Example 2

[0070] A method for preparing a ZnSe@ZnO nano-semiconductor composite material comprises the following steps:

[0071] (1) Preparation of ZnO sol: First, 25 mL of ethylene glycol methyl ether was measured and placed in a clean beaker. Then, 0.26 g of zinc acetate dihydrate was placed in the beaker. The prepared solution was transferred to a magnetic stirrer and stirred thoroughly and evenly for 30 minutes. The solution then became white and turbid. At this time, ethanolamine was slowly added as a stabilizer to make the solution transparent. Finally, the transparent solution was transferred to a 70°C oven and concentrated to 15 mL to form a yellow transparent ZnO sol with a certain viscosity.

[0072] (2) Preparation of ZnO seed layer: FTO was cleaned in an ultrasonic cleaner with acetone, anhydrous ethanol and deionized water for 20 minutes respectively. The cleaned FTO was then placed on a coater and coated with ZnO sol. The coating was performed at low speed (700 rpm), medium speed (1500 rpm) and high speed (3500 rpm). Each spin coating took 10 seconds. The spin-coated sample was placed in an oven at 80°C for 10 minutes. The spin coating and drying process was repeated four times. Subsequently, the sample was placed in a muffle furnace for annealing. The temperature was raised to 400°C at a rate of 6°C / min, maintained for 70 minutes, and finally naturally cooled to room temperature.

[0073] (3) Preparation of ZnO nanorod arrays: First, pour 0.04 mol of zinc nitrate hexahydrate and 0.12 mol of hexamethylenetetramine solution into a beaker at a molar ratio of 1:3. Place them on a magnetic stirrer and stir for 30 minutes. Then, use a rubber-tipped dropper to drop the zinc nitrate hexahydrate solution into the hexamethylenetetramine solution. Continue stirring for 30 minutes to promote the reaction and finally obtain a precursor solution. Next, add 35 mL (70% by volume) of the precursor solution to a reactor containing an FTO substrate on which a ZnO seed layer is grown. Then, place the reactor in a sealed state and react at 90°C for 4 hours to allow the ZnO nanorod array to grow on the surface of the ZnO seed layer. After the reaction is completed, wash the sample with deionized water to remove residual drugs and impurities. Finally, place the sample in an oven at 80°C to dry for use.

[0074] (4) Preparation of ZnSe@ZnO nano-semiconductor composite heterojunction: Add 12 mg of selenium powder, 20 mL of deionized water and 46 mg of sodium borohydride to a small beaker, then place the small beaker into a large beaker filled with deionized water. The liquid level of the large beaker should be higher than that of the small beaker. After the temperature of the magnetic stirrer stabilizes at 55°C, stir for 30 minutes. A transparent solution will be obtained. Then, immerse the reverse side of the ZnO nanorod array grown on the FTO substrate in the above transparent solution and store it in an environment at a temperature of 75°C for 1 hour. After the reaction is completed, wash it with deionized water and finally dry it in air. Thus, a ZnSe@ZnO nano-semiconductor composite heterojunction is successfully obtained, which is recorded as ZS-4.

[0075] Table 1 Process parameters for preparing ZnO / ZnSe composite nanorod arrays at different temperatures

[0076]

[0077]

[0078] Results Analysis

[0079] Figure 1(a) to (d) are XRD patterns of ZnO / ZnSe composite nanorod arrays at different solution temperatures, and several characteristic diffraction peaks were observed. The blue-marked diffraction peaks (110), (200), (211), (200) and (310) are consistent with the standard diffraction peaks of SnO2 (JCPDS No.41-1445) in the substrate FTO material, indicating that the quality of the substrate material has not changed and has been successfully retained. The black-marked diffraction peaks match the standard diffraction peaks (100), (002), (101), (102) (110), (103), (200), (112) and (201) crystal phases of hexagonal wurtzite ZnO (JCPDS 36-1451). This result shows that the prepared sample has a hexagonal wurtzite ZnO crystal structure. And the (002) diffraction peak is the strongest, indicating that the ZnO nanomaterial grows preferentially along the c-axis during the growth process. The present invention also observed very weak diffraction peaks marked with purple red, and observed (100) diffraction peaks and (102) diffraction peaks, which were consistent with the standard diffraction peaks of ZnSe (JCPDS No.10-0105), indicating that ZnSe and ZnO were successfully compounded. When the temperature was 45°C and 55°C, the peaks of the Se element marked with red did not appear in the XRD diagram of the sample. The diffraction peaks (100), (101), (110), (102) and (111) marked with red were consistent with the standard diffraction peaks of Se (JCPDS No.06-0362). When the temperature rose to 65°C and 75°C, the peaks of the Se element could be seen in the XRD diagram.

[0080] Figure 2 (a1) to (d2) are SEM images of ZnO / ZnSe nanoarray composites at different temperatures. Figure 2 It can be seen that when the temperature is 75℃, a large amount of Se single substance covers the surface of ZnO nanorod array, which is consistent with the analysis results of XRD, indicating that high temperature will affect the formation of ZnO / ZnSe heterojunction, forming a large amount of Se single substance, resulting in the inability of ZnSe nanoparticles to effectively grow on the surface of ZnO nanorod array. At 45℃ and 55℃, the surface of ZnO nanorod array is relatively smooth. Combined with the XRD results, the growth of ZnSe nanoparticles on the surface of ZnO nanorod array can be observed, although it is not very obvious. At 65℃, the surface of ZnO nanorod array presents a central bulge. Combined with the XRD results, it can be seen that ZnSe nanoparticles grow on the surface of ZnO nanorod array. Therefore, it can be concluded that when the temperature is 55℃, the growth of ZnSe nanoparticles is best.

[0081] In order to confirm whether there is a heterogeneous structure in the ZnO / ZnSe nanoarray composite material, the chemical state of each element component was analyzed by XPS method. Figure 3(a) to (d). From the measured spectrum of the ZnO / ZnSe nanoarray composite material sample in the Suvery spectrum (a), it can be seen that there are obvious characteristic peaks of Se, C, O and Zn elements, indicating that the elemental composition of the sample includes Se, O and Zn. The strong characteristic peaks centered at 1021.79 eV (Zn2p3 / 2) and about 1044.99 eV (Zn2p1 / 2) in the Zn2p spectrum (b) clearly indicate the presence of zinc oxide. In the Se3d spectrum (c), two deconvolution peaks were observed; the peaks found in the lower binding energy levels (53.81 and 54.68 eV) correspond to Se3d5 / 2 and Se3d3 / 2, respectively, and no peaks of Se single substance were found, which is consistent with the XRD results. The C1s peak in Figure (d) is located at 286.18 eV, so the XPS peak spectra of other elements do not require additional correction.

[0082] The chemical state of each element component was analyzed by XPS method. Figure 4 (a) to (d). From the measured spectrum of the ZnO / ZnSe nanoarray composite material sample in the Suvery spectrum (a), it can be seen that there are obvious characteristic peaks of Se, C, O and Zn elements, indicating that the elemental composition of the sample includes Se, O and Zn. The strong characteristic peaks centered at 1021.96eV (Zn2p3 / 2) and about 1045.05eV (Zn2p1 / 2) in the Zn2p spectrum (b) clearly indicate the presence of zinc oxide. In the Se3d spectrum (c), three deconvolution peaks were observed; the peaks found in the lower binding energy levels (53.90 and 54.81eV) correspond to Se3d5 / 2, respectively. The peak at 55.69eV is the appearance of the selenium-selenium bond peak, indicating the appearance of selenium element after the temperature rises. The C1s peak in Figure (d) is located at 286.57eV, so the XPS peak spectra of other elements do not require additional correction.

[0083] Combination Figure 5 As shown in Table 2, the current-time diagrams and photoelectric performance data of the ZnO / ZnSe composite nanorod array photoelectric device prepared at different temperatures show that when the temperature is 45°C, the dark current of the ZnO / ZnSe composite nanorod array photoelectric device is 4.5×10 -5 A, photocurrent is 3.98×10 -3 A, and its photoelectric sensitivity is 885.6. When the temperature is 55℃, the dark current of the ZnO / ZnSe composite nanorod array photoelectric device is 2.9×10 -5 A, the photocurrent is 8.31×10 -3 A, the photoelectric response sensitivity is 2868.3. When the temperature is 65℃, the dark current of the ZnO / ZnSe composite nanorod array photoelectric device is 3.52×10 -4 A, photocurrent is 6.68×10-3 A, and its photoelectric sensitivity is 885.6. When the temperature is 75℃, the dark current of the ZnO / ZnSe composite nanorod array photoelectric device is 7.8×10 -4 A, photocurrent is 1.99×10 -3 A, its photoelectric sensitivity is 25.5. When the temperature is 55℃, the photoelectric sensitivity of the prepared ZnO / ZnSe composite nanorod array photoelectric device is relatively the best.

[0084] Table 2 Photoelectric performance data of ZnO / ZnSe nanorod array devices prepared at different temperatures

[0085] Sample No. Temperature ℃ Dark current (mA) Photocurrent(mA) Photoelectric sensitivity ZS-1 45 0.45 398.5 885.6 ZS-2 55 0.29 831.8 2868.3 ZS-3 65 3.52 668.41 189.9 ZS-4 75 7.804 199.18 25.5

[0086] In summary, the heterojunction structure composed of ZnSe and ZnO nano-semiconductors of the present invention can significantly increase the separation speed of photogenerated carriers and reduce the recombination efficiency of carriers, thereby greatly improving the photoelectric performance of nano-semiconductor devices. When the temperature is 45°C and 55°C, the peak of Se single substance marked in red does not appear in the XRD diagram of the sample, indicating that there is a heterostructure in the material. When the temperature is 55°C, the dark current of the ZnO / ZnSe composite nanorod array photoelectric device is 2.9×10 -5 A, the photocurrent is 8.31×10 -3 A, the photoelectric response sensitivity is 2868.3.

[0087] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0088] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a ZnSe@ZnO nano-semiconductor composite heterojunction, characterized in that: The following steps are involved: Zinc acetate dihydrate and ethylene glycol methyl ether are mixed, and a stabilizer, ethanolamine, is added thereto to cause an alcoholysis reaction to obtain a ZnO sol; The ZnO sol is coated on the FTO substrate, and then annealed to obtain the FTO substrate with a ZnO seed layer grown thereon; Mixing zinc nitrate hexahydrate and hexamethylenetetramine to obtain a precursor solution, adding the precursor solution to an FTO substrate having a ZnO seed layer grown thereon, and then reacting to grow a ZnO nanorod array on the surface of the ZnO seed layer, thereby obtaining an FTO substrate having a ZnO nanorod array grown thereon; Selenium powder, water and reducing agent sodium borohydride are mixed to obtain a transparent solution, an FTO substrate with a ZnO nanorod array grown thereon is immersed in the transparent solution, and finally the reaction is carried out at 45 to 55° C. for 30 to 60 minutes to obtain a ZnSe@ZnO nano-semiconductor composite heterojunction.

2. The method for preparing the ZnSe@ZnO nano-semiconductor composite heterojunction according to claim 1, characterized in that: During the preparation of ZnO sol, the dosage ratio of zinc acetate dihydrate and ethylene glycol methyl ether was 0.26 g:25 mL.

3. The method for preparing the ZnSe@ZnO nano-semiconductor composite heterojunction according to claim 1, characterized in that: In the precursor solution, the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 1:

3.

4. The method for preparing the ZnSe@ZnO nano-semiconductor composite heterojunction according to claim 1, characterized in that: The usage ratio of selenium powder, water and sodium borohydride is 6-18 mg:20 mL:23-55.2 mg.

5. The method for preparing the ZnSe@ZnO nano-semiconductor composite heterojunction according to claim 1, characterized in that: The annealing temperature of the seed layer is 400-450° C., the annealing time is 70 minutes, and the heating rate is 6° C. / min.

6. The method for preparing the ZnSe@ZnO nano-semiconductor composite heterojunction according to claim 1, characterized in that: The reaction temperature of the precursor solution and the FTO substrate on which the ZnO seed layer is grown is 90° C. to 110° C.

7. The method for preparing the ZnSe@ZnO nano-semiconductor composite heterojunction according to claim 1, characterized in that: The reaction time of the precursor solution and the FTO substrate on which the ZnO seed layer is grown is 4 to 6 hours.

8. The method for preparing the ZnSe@ZnO nano-semiconductor composite heterojunction according to claim 1, characterized in that: The ZnO sol was coated by spin coating at 700 rpm, 1500 rpm and 3500 rpm, respectively, and each spin coating time was 10 s.

9. A ZnSe@ZnO nano-semiconductor composite heterojunction prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for synthesizing ZnO / ZnSe (zinc oxide / zinc selenide) coaxial nano structure through gas-phase anion exchange

    CN103613115A

  • Optoelectronic device ZnO / ZnS heterojunction nano-array film preparing method

    CN105070664A

  • Preparation method of nanometer rodlike structure light positive electrode used for quantum dot sensitization solar battery

    CN107946077A